Stories of Coping with Sickness: Illness Narratives in Early Medieval Chinese Anecdotal Literature - Antje Richter (Chinese Medicine and Culture, 2023)
As basic facts of life, illness and healing occur frequently and in a variety of patterns in Chinese non-medical literature, starting from the earliest sources inscribed on oracle bones and continuing throughout literary history up to the present day. This article looks at illness narratives in early medieval anecdotal literature (3rd to 6th century CE) to understand how the experience of being sick or of attending to the sick was reflected in these socio-literary environments and what rhetorical and ideological roles these narratives played in their larger narrative contexts. By focusing on the experiences of the sick and those around them, this article aims at “Honoring the Stories of Illness,” in Rita Charon’s words, that are hiding in plain sight in much of Chinese non-medical literature.